Terahertz carrier dynamics in graphene and graphene nanostructures - Jensen, Søren A.; Turchinovich, Dmitry; Tielrooij, Klaas Jan; Koppens, Frank; Ulbricht, Ronald; Hertel, Tobias; Narita, Akimitsu; Feng, Xinliang; Müllen, Klaus; Bonn, Mischa (Conference on Lasers and Electro-Optics Europe - Technical Digest, 2014)
Photoexcited charge carriers in 2D graphene and in 1D graphene nanostructures were studied with optical pump-THz probe spectroscopy. We find efficient hot-carrier multiplication in 2D graphene, and predominantly free carrier early-time response in 1D nanostructures.
CRIS-Team Scopus Importer:2023-03-20